A Program of Nutritional Education in Schools Reduced the Prevalence of Iron Deficiency in Students. (27th March 2011) - García-Casal, María Nieves; Landaeta-Jiménez, Maritza; Puche, Rafael; Leets, Irene; Carvajal, Zoila; Patiño, Elijú; Ibarra, Carlos
Abstract : The objective was to determine the prevalence of iron, folates and retinol deficiencies in school children and to evaluate the changes after an intervention of nutritional education. The project was developed in 17 schools. The sample included 1, 301 children (678 males and 623 females). A subsample of 480 individuals, was randomly selected for drawing blood for biochemical determinations before and after the intervention of nutritional education, which included in each school: written pre and post-intervention tests, 6 workshops, 2 participative talks, 5 game activities, 1 cooking course and 1 recipe contest. Anthropometrical and biochemical determinations included weight, height, body-mass index, nutritional status, hematocrit, serum ferritin, retinol and folate concentrations. There was high prevalence of iron (25%), folates (75%) and vitamin A (43%) deficiencies in school children, with a low consumption of fruit and vegetables, high consumption of soft drinks and snacks and almost no physical activity. The nutritional education intervention produced a significant reduction in iron deficiency prevalence (25 to 14%), and showed no effect on vitamin A and folates deficiencies. There was a slight improvement in nutritional status. This study shows, through biochemical determinations, that nutritional education initiatives and programs have an impact improving nutritional health in school children.